Treatment of a glucose-starch waste by the anaerobic filter process - Cronje, Carl Peter Roche (Department of Civil Engineering, 2024)
[page 22, 159 missing] An investigation was carried o~t_to determine whether the strong glucose-starch waste_di§charged from an industry in Bel lvi lie could be treated by means of. an anaerobic filter. At present the waste 1s being treated anaerobically in two clarigesters. An experimental anaerobic filter was bui It and 0 operated for 129 days at an average temperat~re Qf.34 C and for a further 52 days at a reduced average temperature of 25°C. The waste was wet I balanced in that al I _the essential nutrients were present in sufficient.concentration for the anaerobic process. The statisticaJ mean COD value Qf the raw waste unfiltered was 10700 mg/I, filtered 8500 mg/I and the pH 4,14. A constant COD value of 7000 mg/I wa, used throughout the investigation. Recycling of the content§ in the filter was necessary to maintain the pH in the range 6,4 - 7,4. The maximum load handled by the ana~robic filter was 5,38 kg COD/m 3/day (based on total volume of~filter) and 8,38 kg COD/m 3/day (based on hydraul_lc volume) at retention times of 1,30 days {total volume) and 0,83 days (hydraulic volume). Reduction in COD ranged from 97,1 ( i i ) percent at 2,591 kg COD/m3/day (total volume) to 90 percent at 5,38 kg COD/m 3/day (total volume). At loads higher than 5,38 kg COD/m 3/day, the filter showed signs of failure. Failure 1s closely related to.the sludge loss. in the~fluent and it is concluded that the sol ids retention time is reduced if the concentration of sol id$ increases in the effluent. Furthermore, if the __ effluent_sQI ids __ concentration remains constant, at different loading rates, the sol ids lost per day remain prqportion~I _to.the feed rate. and constant S.R.T. is maintained. These signs _of fai !ure were due to reduction of the S.R.T., thus conforming to the general theory of anaerobic digestion. Further operation at a reduced average temperature of 25°C showed that half the l9ad_c9uld be treated with the same degree of efficiency as was the case at the higher temperature. The clarigesters at preseot in use Qperate at an 0 average temperature of 23 C thr9ughout the_year and_h~ndle a load of 1,78 kg COD/m 3/day based on the total volume of the clarigester at an average H.R.T. of 6 days. A comparison between the perf9rmance_ of the clarigesters and the experimental anaerobic filter at approximately 23°C, indicates that the anaerobic filter has no significant advantages over the clarigesters. ( i i i ) It is recommended that : the existing clarig~sters be retained; the loading capacity of tbe clarigesters be raised by increasing the temperature inside the digester compartment from 23°C to approximately 35°C; the liquidsol ids separation scheme of the clarigesters be modified to positively control the sludge age.